Pengembangan Bahan Ajar Kalkulus 1 Berbasis Konseptual Untuk Mahasiswa Teknik Informatika Universitas Islam Syekh Yusuf-Tangerang - Qoiriyah, Waqidatul; Syam, Syahriani (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2021)
This research is focused on developing calculus 1 teaching materials for students of the Informatics Engineering Study Program, Faculty of Engineering, Islamic University, Sheikh Yusuf Tangerang. The reasons for the development of teaching materials were, among others, the low scores of national mathematics exams, and the unavailability of handbooks that could improve basic mathematics skills to support calculus courses.This research aims to produce products in the form of calculus 1 teaching materials for students of the informatics engineering study program, Faculty of Engineering, Islamic University Sheikh Yusuf Tangerang. The method used in this research is the method of research and development (Research and Development). The development model chosen in this study is the Borg and Gall model. The stages in this research include: (1) studying research findings (preliminary study and needs analysis), (2) developing the product, and (3) field testing and revising. This study uses a research and development research method wherein the reporting uses qualitative and quantitative approaches. The results of this study classify teaching materials into three subjects, namely theory, introductory questions, and stabilization questions in each chapter. The validation of the study was carried out by 3 expert judgments, namely the validator 1, 93.7%, the validator 2, 89.5%, and the validator 3, 85.4%, so that it had an average relative score of 89.5 with the category of teaching materials good / feasible to use.